2020
DOI: 10.7759/cureus.9509
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Protocol to Determine the Most Effective Strategies to Reduce Computed Tomography Usage in the Emergency Department

Abstract: This study describes the protocol for a systematic review and meta-analysis. The primary objective of the review is to identify experimental studies assessing the effectiveness of interventions that aim to reduce the proportion of computed tomography (CT) in emergency departments (EDs). Data permitting, our secondary objectives will be to assess the impact of reduction in CT utilization on the length of stay, admission to hospital, and uptake/satisfaction with the intervention. When available, balancing measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The aim of the second review round will be to identify which studies meet all inclusion criteria. Researchers will utilize a standardized screening tool, adopted from Elzinga et al, to determine the inclusion eligibility of every study [10]. The tool consists of four questions, each addressing a specific inclusion/exclusion criterion.…”
Section: Abstract Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the second review round will be to identify which studies meet all inclusion criteria. Researchers will utilize a standardized screening tool, adopted from Elzinga et al, to determine the inclusion eligibility of every study [10]. The tool consists of four questions, each addressing a specific inclusion/exclusion criterion.…”
Section: Abstract Reviewmentioning
confidence: 99%
“…FIGURE 1: Overview of a standardized full-text screening tool Adapted from: Elzinga et al (2020)[10] …”
mentioning
confidence: 99%
“… 1 In the USA, CT radiation doses account for over half the population effective dose received from medical sources. 2 Even with this knowledge, the total number of yearly CT examinations grows. 3 , 4 Large‐scale studies have indicated the detrimental impact of ionizing radiation on human tissue, with the increased radiosensitivity of pediatric populations compared to adult populations, an area of particular concern.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation doses to the patient during computed tomography (CT) procedures are among the highest in diagnostic radiology 1 . In the USA, CT radiation doses account for over half the population effective dose received from medical sources 2 . Even with this knowledge, the total number of yearly CT examinations grows 3,4 .…”
Section: Introductionmentioning
confidence: 99%